Etika Bisnis Islam dalam Sistem Menabung Bank Sampah - Wiwin Mariyana; Haura Sabita Putri; Indraswari Pramudaning Tyas (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Waste piles in Indonesia are increasing year by year. Waste bank is considered as a real solution to the waste problem. During this time, waste bank has only been available around the community. Bank Sampah Pijar Area is a waste bank which is located at UIN Raden Mas Said Surakarta. As a waste bank under the Islamic campus authority, the principles of running its business must also be on Islamic priciples. Therefore, the researcher aims to examine the Islamic business ethics run by the Bank Sampah Pijar Semesta. The purpose of this study is to harmonize Islamic principles that should be brought with the Islamic campus basic. The method used in this research is qualitative with a phenomenological approach by taking samples using the purposive sampling. The results of the study show that initially the waste bank had implemented the principles of Unity, Balance/Justice, Free Will, Responsibility, and Truth: Virtue and Honesty. This research can contribute to businessman and environmental hygiene in the campus area.